Pengaruh Citra Merek dan Harga Terhadap Keputusan Pembelian Pasta Gigi Close Up di Pondok Pesantren Darul Falah V - Robiatul Aslamiyah (Prodi Manajemen Fakultas Ekonomi Universitas Hasyim Asy'ari Tebuireng Jombang, 2020)
The purpose of this research is to analyze the influence of the brand image and the price toward the decision to buy the toothpaste product of Closeup in Islamic boarding school of Darul falah V, Cukir Diwek Jombang by using research technique of quantitative and method of causal research method. The data was got from the survey and questionnairs distributed to 40 students of islamic boarding school of Darul Falah V, Cukir Diwek Jombang. The purposive sampling was used to take the sample consisting of 40 students by thge specific critrerias related to the research purpose in order to answer the research problem. The technique of data anaysis used multiple linear regression. The hyphothesis testing showed the results that: (1) The brand image partially and significantly influences the decision to buy the toothpaste of Closeup in Islamic boarding school of Darul Falah V, Cukir Diwek Jombang. (2) The price does not partially and significantly influences the decision the decision to buy the toothpaste of Closeup in Islamic boarding school of Darul Falah V, Cukir Diwek Jombang and (3) The brand image and the price simultaneously influence the decision to buy the toothpaste of Closeup in Islamic boarding school of Darul Falah V, Cukir Diwek Jombang.